Identification of frame models under unmeasured base motion: experimental validation. (2017) - Sepe, Vincenzo; Valente, Claudio; Zuccarino, Luigia; Siano, Rossella; Iezzi, Fabrizio
Abstract: Structural Health Monitoring (SHM) is an area of great interest in civil engineering, and in this framework very reliable techniques for modal identification in the linear field are widely used. However, most of them require the knowledge of both forcing actions and structural response (e.g. for transient oscillations, as seismic-induced ones) or long-duration - or even stationary - output-only measures of the response (e.g. in case of wind-induced actions). For a frame structure subject to transient and unmeasured base motion, as considered here, a technique proposed by one of the writers in previous papers requires only the structural response at the floor levels, without any quantitative information on the excitation. It starts from the observation that the ratios between the Fourier transforms of the structural responses at different levels are independent on the base motion characteristics and, therefore, can be expressed as a function of the modal parameters. In particular, the uniqueness of the solution was demonstrated when the structural response is known for at least three different floor levels. To validate the procedure, this paper describes the results of an experimental campaign, that was performed on a laboratory model simulating a three storey shear-type plane frame subject to different types of base motions.